A highly efficient method for the production and purification of recombinant human CXCL8 - McKenna,S; Giblin,SP; Bunn,RA; Xu,Y; Matthews,SJ; Pease,JE (PLoS One, 2021)
Chemokines play diverse and fundamental roles in the immune system and human disease, which has prompted their structural and functional characterisation. Production of recombinant chemokines that are folded and bioactive is vital to their study but is limited by the stringent requirements of a native N-terminus for receptor activation and correct disulphide bonding required to stabilise the chemokine fold. Even when expressed as fusion proteins, overexpression of chemokines in E. coli tends to result in the formation of inclusion bodies, generating the additional steps of solubilisation and refolding. Here we present a novel method for producing soluble chemokines in relatively large amounts via a simple two-step purification procedure with no requirements for refolding. CXCL8 produced by this method has the correct chemokine fold as determined by NMR spectroscopy and in chemotaxis assays was indistinguishable from commercially available chemokines. We believe that this protocol significantly streamlines the generation of recombinant chemokines.